Рекомендаційна модель для підбору кросфіт тренувань - Залуський , Марко Анатолійович (Національний університет “Львівська політехніка”, 2021)
Бакалаврська кваліфікаційна робота виконана студентом групи КН-410 Залуським Марком Анатолійовичем. Тема «Рекомендаційна модель для підбору кросфіт тренувань». Робота направлена на здобуття ступеня бакалавр за спеціальністю 122 «Комп’ютерні науки». Метою роботи є розробка інтелектуальної системи, що буде видавати кросфіт – комплекси, що має полегшити процес систему підбору тренувань для певного рівня атлетів. Об’єктом дослідження є визначення адаптивної програми тренувань. Предметом дослідження є процес створення тренувань відомих атлетів. Методами дослідження є алгоритми машинного навчання, а саме рекомендаційна система на основі зважених асоціативних правил. Науковою новизною є створення рекомендаційної моделі додатку, яка зможе самостійно будувати кросфіт комплекси. Практична цінність. Використання додатку дозволить зекономити користувачу на тренуваннях у персонального тренера та допоможе покращити його фізичні дані. With each passing day, a healthy lifestyle is becoming more and more popular among the population. Sport is an important element of a healthy person's life. Not only can it increase muscle or reduce the waistline, we can improve our health, reduce the likelihood of certain diseases, such as atherosclerosis or diabetes. Sport has a positive effect on the work of the whole organism. It should be noted that exercise is a great cure for stress and depression. After physical activity, the human body begins to actively synthesize the neurotransmitters serotonin, the so-called "happiness hormone" and dopamine. These biologically active substances affect mood, sexual desire, appetite and motivation. Recently, such a sport as CrossFit is gaining popularity. It allows a person to improve the state of general physical training, increase their endurance. All workouts differ in a set of exercises. None of them are repeated, which is a huge plus, because there is a lack of routine. Since we live in a world of technology, we look for resources in the training process that can help us in the training process. Currently, there are a sufficient number of sites where you can find various crossfit complexes, but none of them has a system that independently created training for a particular athlete. In addition, the existing system does not have extensive capabilities of the complex. Mostly on the sites you can find complexes by name or by date of creation. Thus, the main task of the bachelor's qualification work is to develop a crossfit site with advanced features, namely the construction of a training program exclusively for the level of a particular athlete. In addition, the site will be upgraded to search for existing complexes and the ability to scale them to the user.
Keywords: рекомендаційна модель, кросфіт, тренування